Critical capabilities and competencies for knowledge organizations. (2019) - Cegarra Navarro, Juan Gabriel; Garcia-Perez, Alexeis; Wakabayashi, Susan; Bedford, Denise A. D, 1990-; Thomas, Margo
No abstract available